Common challenges faced by early-career researchers in Latin American and small U.S. universities - Daniela Cejas; Fatima Rodriguez Acosta; Juan Rivera-Correa (mBio)
ABSTRACT Early-career researchers from Spanish-speaking Latin American countries and small U.S. universities are underrepresented in international scientific databases. They have geographical importance, infectious disease endemicity, and exceptional researchers in microbiology, but these factors do not translate to representation in high-impact scientific publications. Many reasons could be involved, including financial burdens such as the inability to pay article processing charges. Additional teaching, institutional, and service responsibilities also highly influence their research productivity. Despite this, they are expected to publish high-impact articles, and their career development highly depends on it. There is an opportunity for global peer collaboration to tackle this inequity and uplift underrepresented scientists, which will ultimately provide benefits and sustainability to the global microbial sciences.